Online interest in radical Islam and terrorist attacks - Marcella Nicolini; Fabio Sabatini; Dean Fantazzini (Peace Economics, Peace Science and Public Policy (PEPS), 2025)
This study investigates the link between terrorist attacks and public interest in radical Islam and violent extremism, using monthly data from 150 countries between 2004 and 2015. Employing a dynamic common correlated effects (DCCE) estimator to account for potential cross-country correlations, our analysis reveals that attacks carried out in the name of Islam significantly drive online searches for sensitive keywords. Specifically, terms suggesting violent actions, such as "beheadings," and explicitly jihad-related terms show stronger correlations, indicating heightened interest in the terrorists' actions and messages. Our findings suggest that terrorist attacks not only occur in areas where public attention to terrorism is already heightened but also intensify interest in violent extremism within those regions. This amplification may contribute to terrorists' objectives by increasing the public visibility they seek.
Keywords: C33; F50; H56; 320; dynamic common correlated effects estimator (DCCE); Google searches; islamist extremism; terrorism